Freezing the Biological Clock: The Experience of Undergoing Social Egg Freezing to Delay Child-Bearing - Isaacson, Jordanna; Daniluk, Judith C. (Canadian Journal of Counselling and Psychotherapy, 2020)
In 2012, egg freezing was made available as an elective procedure for healthy reproductive-age women to attempt to preserve their fertility. To date, limited research has examined the experiences of women who have undergone this procedure or the meanings they attribute to this phenomenon. This study was designed to address this gap in the literature, using a hermeneutic phenomenological methodology. The research question that guided this inquiry was: “What is the meaning and experience of undergoing social egg freezing for the purpose of delaying child-bearing?” In-depth qualitative research interviews were conducted with six women between the ages of 28 and 41. Interviews were transcribed verbatim and a thematic analysis was performed. Six common themes emerged from the women’s stories: (a) the sense of reducing the pressure to have a child, (b) the sense of taking control and of reproductive agency, (c) the sense of personal empowerment and acceptance, (d) the sense of feeling fortunate, (e) the sense of keeping reproductive and parenting options open, and (f) openness and support. The findings highlight the challenges and the perceived benefits of egg freezing to delay child-bearing and present important implications for counselling practice.